Application servers for e-business - Lindgren, Lisa (Auerbach, 2001)
The modern application server is a complex platform that is the linchpin of an enterprise environment that includes a very wide range of technologies-web document formatting, web protocols, server-side scripts, servlets, applets, programming languages, distributed object technologies, security capabilities, directory and naming services, load balan.